The Boustrophedonic Turns Of Suffering in Faithful And Virtuous Night by Louise Glück - Marie Olivier (Transatlantica)
In Louise Glück’s latest collection Faithful And Virtuous Night (2014), the poet’s swerving toward a more narrative form contributes—surprisingly perhaps—to revising the traditional Romantic chiasmus that exists between the mourning or suffering personae and their environment. This article attempts at capturing how Glück’s choices in lineation in her verse expose the intrinsic loss and hiatus there is between language and the world. It means to illustrate the way time and lyric subjectivity are structured in Glück’s latest collection.